Analysis Of The Influence Of Supervision, Work Skills, And Salary On Employee Performance In Pt. Persada Indonesia Workshop In Sukabumi District - Ferdinandus Sampe; Norvadewi Norvadewi; Arifin Bagea; Rebecha Prananta (IAIN Palopo, 2022)
The purpose of this study was to determine the effect of supervision, work skills, and salary simultaneously and partially have a significant effect on employee performance at PT. Persada Indonesia in Sukabumi Regency and analyze the dominant influence among the variables of supervision, work skills, and salary which have a dominant effect on employee performance in PT. Persada Indonesia in Sukabumi Regency. This type of research is quantitative research based on hypothesis testing. The population and sample of this research are all employees of PT. Persada Indonesia who have worked for more than 2 years are 99 employees with a sample of 99 people. Methods of data analysis using multiple linear regression. The results of this study indicate that supervision has no significant effect on employee performance. Work skills have had a significant influence on employee performance. Investment has had a significant influence on employee performance at PT. Persada Indonesia in Sukabumi Regency.